Adaptive Queue Management Scheme For Internet Congestion Control - Chong , Poh Kit (2003)
This thesis presents a new queue management scheme for congestion control in TCP/IP(Transmission Control protocol/Internet protocol) Networks. Congestion control in TCP/IP networks is very important to prevent congestion collapses which can lead to a loss in Internet services.